Long-term sensory stimulation therapy improves hand function and restores cortical responsiveness in patients with chronic cerebral lesions. Three single case studies - Kattenstroth, Jan-Christoph; Kalisch, Tobias; Peters, Soren; Tegenthoff, Martin; Dinse, Hubert R. (Frontiers in Human Neuroscience, 2012)
Rehabilitation of sensorimotor impairment resulting from cerebral lesion (CL) utilizes task specific training and massed practice to drive reorganization and sensorimotor improvement due to induction of neuroplasticity mechanisms. Loss of sensory abilities often complicates recovery, and thus the individual’s ability to use the affected body part for functional tasks. Therefore, the development of additional and alternative approaches that supplement, enhance, or even replace conventional training procedures would be advantageous. Repetitive sensory stimulation protocols (rSS) have been shown to evoke sensorimotor improvements of the affected limb in patients with chronic stroke. However, the possible impact of long-term rSS on sensorimotor performance of patients with CL, where the incident dated back many years remains unclear. The particular advantage of rSS is its passive nature, which does not require active participation of the subjects. Therefore, rSS can be applied parallel to other occupations, making the intervention easier to implement and more acceptable to the individual. Here we report the effects of applying rSS for 8, 36 and 76 weeks on the paretic hand of 3 long-term patients with different types of CL. Different behavioral tests were used to assess sensory and/or sensorimotor performance of the upper extremities prior, after, and during the intervention. In one patient, the impact of long-term rSS on restoration of cortical activation was investigated by recording somatosensory evoked potentials. After long-term rSS all three patients showed considerable improvements of their sensory and motor abilities. In addition, almost normal evoked potentials could be recorded after rSS in one patient. Our data show that long-term rSS applied to patients with chronic CL can improve tactile and sensorimotor functions, which, however, developed in some cases only after many weeks of stimulation, and continued to further improve on a time scale of months.